Adoption of improved tef and wheat production technologies in crop-livestock mixed systems in northern and western Shewa zones of Ethiopia - Hassan, Rashid M. (University of Pretoria, 2013)
Thesis (PhD (Agricultural Economics))--University of Pretoria, 2008.